SPEECH ACT ANALYSIS OF THE PARTICIPANTS’ SPEECHES IN THE STUDY OF THE U.S INSTITUTES (SUSI) PROGRAM - Sitti Adhila Suprihana; Noor Eka Chandra; Elsa Rosalina (Universitas Lambung Mangkurat, 2025)
Research related to speech acts in speeches is frequently conducted, particularly in the context of speeches delivered by political and prominent figures. However, speeches by international exchange program students receive less attention despite their potential impact to influence audiences. Moreover, this study investigates the types of illocutionary speech acts employed by 20 undergraduate participants who were part of the 2021 Study of the U.S. Institutes (SUSI). The theme of the analyzed speeches is